2005
DOI: 10.1002/nur.20096
|View full text |Cite
|
Sign up to set email alerts
|

Higher‐order factor analysis of an instrument with dichotomous data

Abstract: This article reports the use of higher-order factor analysis to examine the underlying dimensions of an instrument designed to measure community acceptance of nurse practitioners/physician's assistants. The instrument consisted of both dichotomous and Likert scale items. Use of factor analysis with dichotomous data is controversial. Higher-order factor analysis provides a potential solution to this dilemma. Following initial factor analysis using maximum likelihood extraction with oblique rotation, the factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
1
Order By: Relevance
“…This idea is not new, and both classical and modern psychometric theories have developed approaches to test the validity of such scales. In classical test theory a second‐order factor analytic approach has been used to confirm higher‐order dimensions, although its utility with just two or three factors is unclear (Baldwin et al , 2005). In modern test theory, most recently, multidimensional Rasch models have been proposed, which also test for higher‐order measurement constructed from valid subscales, although this approach has yet to gain widespread use (Briggs & Wilson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This idea is not new, and both classical and modern psychometric theories have developed approaches to test the validity of such scales. In classical test theory a second‐order factor analytic approach has been used to confirm higher‐order dimensions, although its utility with just two or three factors is unclear (Baldwin et al , 2005). In modern test theory, most recently, multidimensional Rasch models have been proposed, which also test for higher‐order measurement constructed from valid subscales, although this approach has yet to gain widespread use (Briggs & Wilson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Given several of the variables were highly correlated, this suggested that certain factors might measure aspects of common underlying dimensions. As summarized by Baldwin et al (2005), the use of factor analysis with dichotomous variables is controversial, but many statistical experts agree on its use, with caution, and many studies have used techniques to apply factor analysis to dichotomous data (e.g., Banos & Franklin, 2002;Bartholomew, 1980;Gorsuch, 1983;Mundform, Bradley & Whiteside, 1993;Tabachnick & Fidell, 2001;Tomas-Sabado, & Gomez-Benito, 2005). Specifically, given the aim of this research question was to examine components (factors) among dichotomous variables in a measure, in order to validate underlying constructs, the use of factor analysis was justified.…”
Section: Hypothesis 1c): Components Of Fidelity Elements To Conduct T...mentioning
confidence: 99%
“…Тези методи от по-висок порядък подсилват надеждността на факторната структура при наличие на противоречиви данни и включват извършването на два факторни анализа. Първоначалният се състои от противоречиви отговори за определяне на факторите от по-висок порядък, а вторият се състои от факторите от по-нисък порядък за установяване на фактори, които са от по-висок порядък и са доминиращи [13].…”
Section: схващания и нагласи за аналгетицитеunclassified